2023
DOI: 10.3390/ma16216928
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing Technologies for Fabrication of Magnetic Materials Based on Metal–Polymer Composites: A Review

Alina Mazeeva,
Dmitriy Masaylo,
Nikolay Razumov
et al.

Abstract: Additive manufacturing is a very rapidly developing industrial field. It opens many possibilities for the fast fabrication of complex-shaped products and devices, including functional materials and smart structures. This paper presents an overview of polymer 3D printing technologies currently used to produce magnetic materials and devices based on them. Technologies such as filament-fused modeling (FDM), direct ink writing (DIW), stereolithography (SLA), and binder jetting (BJ) are discussed. Their technologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 163 publications
(345 reference statements)
0
1
0
Order By: Relevance
“…Therefore, a compromise between eddy current losses and fill factor has to be made. The topic of fill factor is also especially interesting, as research on soft-magnetic metal-polymer composites has shown a strong non-linear connection between fill factor and magnetic properties as well as losses [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a compromise between eddy current losses and fill factor has to be made. The topic of fill factor is also especially interesting, as research on soft-magnetic metal-polymer composites has shown a strong non-linear connection between fill factor and magnetic properties as well as losses [19][20][21].…”
Section: Introductionmentioning
confidence: 99%